2017
DOI: 10.1620/tjem.243.205
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Combination of Tuberculin Skin Test and Interferon-Gamma Release Assay in Diagnosing Children with Tuberculosis

Abstract: Japan is still designated as a medium incidence country, worldwide. Although the definitive diagnosis of tuberculosis is made by detecting pathogen from tissue specimens, collecting those from children is physically difficult. Therefore, we must frequently depend on the results of tuberculin skin test (TST) or interferon-gamma release assay (IGRA). However, the value of IGRA in diagnosing tuberculosis in infants remains unclear. We implemented TST and IGRA concurrently and examined the significance of combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Current literature comparing the performance of IGRA (Quantiferon and T-Spot) and TST to identify TB infection in young children reveals limited evidence and conflicting results [5,[30][31][32][33]. Studies focusing on performance of T-Spot in comparison to TST may show discordant results with TST positive and T-Spot negative cases.…”
Section: Viability Of T-spot In Contact Infantsmentioning
confidence: 99%
“…Current literature comparing the performance of IGRA (Quantiferon and T-Spot) and TST to identify TB infection in young children reveals limited evidence and conflicting results [5,[30][31][32][33]. Studies focusing on performance of T-Spot in comparison to TST may show discordant results with TST positive and T-Spot negative cases.…”
Section: Viability Of T-spot In Contact Infantsmentioning
confidence: 99%
“…The median number of contacts undergoing advanced imaging was relatively small, at 32. Twelve studies examined children to adolescents [ 13 – 16 , 18 , 21 , 23 – 25 , 27 , 28 , 30 ], while the other studies included adults. One study was conducted on contacts infected with HIV [ 35 ], while the other 24 studies were conducted in immunocompetent contacts.…”
Section: Main Textmentioning
confidence: 99%
“…Recent WHO surveys found that one-third of the world’s population was latently affected by tuberculosis, and over 1.5 million patients die annually. Clinical symptoms, radiography, the tuberculin skin test (TST), and the interferon-gamma release assay (IGRA) are the most critical components of a patient’s diagnosis ( Shimizu and Mori 2017 ). Pharmacotherapy is recommended as the initial treatment for tuberculosis patients ( Suarez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%